Inhibition and synchronisation of tremor induced by a muscle twitch. - Bathien, N (1980)
The effects of a muscle twitch on the tremor of the extensor indicis muscle and of the tibial anterior muscle have been recorded in 14 patients with essential tremor and in 10 patients with Parkinson's disease. The muscle twitch evoked by the electrical stimulation of the motor nerve inhibits the tremor and synchronises it. The mean duration of the inhibition is 92.1 +/- 6.8 ms for essential tremor and 183.0 +/- 16.8 ms for Parkinsonian tremor. This inhibitory phase lasts longer when the muscle twitch is induced during the second half of the Parkinsonian tremor cycle. The effects of voluntary contraction and of unloading suggest that inhibition and resetting of the tremor can be attributed to the autogenic mechanism induced by Ib fibres discharges. The presence of a rhythmic inhibition in the cycle of Parkinsonian tremor accounts for the longer duration of the inhibitory phase. In practice, these techniques aid the diagnosis of tremor in these two conditions, for example they assist the identification of low frequency essential tremor and of postural tremor in Parkinson's disease.